2020
DOI: 10.1021/acsnano.0c05459
|View full text |Cite
|
Sign up to set email alerts
|

Intersubband Relaxation in CdSe Colloidal Quantum Wells

Abstract: The dynamics of intersubband relaxation are critical to quantum well technologies such as quantum cascade lasers and quantum well infrared photodetectors. Here, intersubband relaxation in CdSe colloidal quantum wells, or nanoplatelets, is studied via pump–push–probe transient spectroscopy. An initial interband pump pulse is followed by a secondary infrared push excitation, resonant with intersubband absorption, which promotes electrons from the first conduction band of the quantum well to the second conduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…371 Three pulse pump−push−probe experiments, in which a secondary "push" pulse is resonant with photoinduced intersubband transitions, revealed a slowing of electron cooling at 5 K (350 fs) compared to 300 K (700 fs) for one sample, as well as ligand-dependent cooling that was faster for phosphonates (350 fs) than thiolates (800 fs). 329 Intraband relaxation in NPLs is slowed at higher excitation intensities. For example, measurements of optical pumping followed by a photoelectron probe from Sippel et al shown in Figure 28 indicate that the kinetic energy of liberated electrons falls from an effective temperature of 3000 K to ∼650 K in 1 ps, but this is followed by a much slower fall to ambient temperature.…”
Section: Photoluminescence Spectra and Quantum Yieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…371 Three pulse pump−push−probe experiments, in which a secondary "push" pulse is resonant with photoinduced intersubband transitions, revealed a slowing of electron cooling at 5 K (350 fs) compared to 300 K (700 fs) for one sample, as well as ligand-dependent cooling that was faster for phosphonates (350 fs) than thiolates (800 fs). 329 Intraband relaxation in NPLs is slowed at higher excitation intensities. For example, measurements of optical pumping followed by a photoelectron probe from Sippel et al shown in Figure 28 indicate that the kinetic energy of liberated electrons falls from an effective temperature of 3000 K to ∼650 K in 1 ps, but this is followed by a much slower fall to ambient temperature.…”
Section: Photoluminescence Spectra and Quantum Yieldsmentioning
confidence: 99%
“…112 In contrast to CdSe QD, where intraband relaxation times are reported to be in the tens of picoseconds, 328 NPL intersubband relaxation is subpicosecond. 329 3.4. Linear and Circular Polarization of Optical Properties.…”
Section: Photoluminescence Spectra and Quantum Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…51 An additional possibility for the faster cooling of thinner CQWs is that surface phonon modes (not just LO phonons) play an important role in cooling, which was also suggested previously. 55,56 The line-shape of the intersubband transition also reveals fluence-dependence of the dynamics. The cooling times observed here under low fluence excitation are much faster than those reported at higher fluence.…”
Section: Resultsmentioning
confidence: 96%
“…As the effective mass also shifts the energetic levels, resonances of heavier particles densify in the low-frequency regime. A rather small dephasing rate of Γ = 1.5 ps –1 at room temperature for all charged particles is used, and the sharp absorption characteristics remain visible. In contrast, the excitonic mobility is orders of magnitude smaller due to its polarization nature.…”
Section: Results and Discussionmentioning
confidence: 99%